Ag decorated G‐C3N4/black titanium oxides composite for the destruction of environmental pollutant under solar irradiation. (21st August 2019) - Masih, Dilshad; Ma, Yuanyu; Rohani, Sohrab
Abstract : Research on the synthesis of advanced composite materials is an important area of research on the visible‐active photodegradation of environmental pollutants. Novel hybridized structures of graphitic carbon nitride (g‐C3 N4 ) are synthesized by a facile one‐step in‐situ method. Black titanium oxides, TiO, Ti2 O3, a mixture of TiO + Ti2 O3, and a reference material, white TiO2 P25, are used for the synthesis of the hybridized g‐C3 N4 and further decorated with Ag nanoparticles. Physicochemical and optical properties of the obtained materials are characterized by various techniques. XRD patterns revealed that the structural regularity of g‐C3 N4 and titanium oxide(s) is maintained in the composites. However, the main diffraction peak for g‐C3 N4 is prominently shifted to a lower 2‐theta along with a decrease in the intensity, indicating the formation of g‐C3 N4 nanosheet heterojunction. Vibrational spectra of the composites showed signature IR peaks for g‐C3 N4 and demonstrated an enhancement in the vibrations after modifications, and further supported the XRD results. A distinct red‐shift in the optical spectra of g‐C3 N4 upon modifications with black titanium oxide(s) demonstrated an enhanced absorbance of visible light, yet on the contrast white TiO2 P25 showed a blue‐shift. Under the experimental conditions of simulated solar light, pristine g‐C3 N4, and its composites g‐C3 N4 /TiO and g‐C3 N4 /Ti2 O3 showed moderate activity for the photodegradation of an organic pollutant, rhodamine B. Interestingly, a synergistic enhancement in the photoactivity is demonstrated by the g‐C3 N4 modified with a mixture of black titanium oxides (g‐C3 N4 /TiO + Ti2 O3 ). On the other hand, the composite synthesized by a post‐synthesis method is found less effective in photodegradation reaction.